Efektivitas BLT PKH terhadap Kesejahteraan Keluarga Tukang Becak di Kelurahan Kartini Kota Binjai - Muhammad Ihsan Alfianiyus; Mia Aulina Lubis (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
BLT PKH is one form of government program that focuses on assisting the poor in meeting their needs, improving the welfare of poor families, and reducing poverty in Indonesia. BLT itself originated from 2005 presidential instruction number 12, which was carried out by the President who served at that time, Susilo Bambang Yudhoyono, and his deputy, Jusuf Kalla. The purpose of this research is to measure the effectiveness of BLT PKH in improving the welfare of the families of pedicab drivers in Kartini Village, Binjai Kota, as BLT recipients, based on theories, variables, and also real events in the field. This research is qualitative, with data collection techniques carried out by combining (triangulation) the processes of in-depth interviews, observation, and documentation, which are then analyzed by researchers qualitatively and concluded with drawing conclusions from the results of the research that has been done. The results of the family welfare research are not fully influenced by the effectiveness of BLT PKH. It is recommended that the government continue to supervise and program similar assistance programs to continue to overcome the problems of poverty in Indonesia.